KEARIFAN LOKAL MASYARAKAT DUSUN PINANG DALAM MENJAGA KEBERADAAN TEMBAWANG DI DESA KECURIT KECAMATAN TOHO KABUPATEN MEMPAWAH - Teryola, Afia Sunarti; Roslinda, Emi; Zainal, Sofyan (MAKILA, 2024)
Local wisdom is knowledge, norms, regulations, skills and beliefs of the community born from ancestors who have positive values guaranteed to be passed down from generation to generation and become a local culture that is adhered to by the people of Dusun Pinang in their daily lives. This research aims to explain forms of local wisdom and the role of local wisdom in the Tembawang community. Data was collected through a survey using interview techniques and a questionnaire. The census took respondents—the research results regarding forms of local community wisdom that support Sembawang management in the Dusun Pinang community. People believe in the existence of this myth, which makes them not dare to damage Tembawang by clearing the land. Regulation, prohibition of cutting down trees in Tembawang, this regulation is designed to avoid damage to Tembawang. Skills: The community uses Tembawang land to plant trees that produce fruit. The role of wisdom in the form of weeding is done to maintain the fertility of the Tembawang land so that it can be helpful and has potential. The role of local wisdom in the form of customary legal sanctions aims to prevent people from daring to carry out logging and damage in the Tembawang area.